EFL Teachers’ Experiences in Teaching Reading Texts Incorporating Local Wisdom - Selamet Riadi Jaelani; Nunung Suryati; Yazid Basthomi; Nurenzia Yannuar; Baiq Suprapti Handini; Ahmad Munawir (International Journal of Language Education, 2026)
This study examines EFL teachers' experiences in teaching reading texts that incorporate local wisdom to understand how culturally relevant materials impact classroom instruction and student engagement. This study employed a qualitative method to explore EFL learners' perceptions of reading materials containing local culture. A total of 15 teachers were selected as participants using purposive random sampling based on specific criteria: (1). have completed a reading course integrated with local culture; (2). a higher concentration of data in the 78–88 score range with fewer responses in the lower range in said teaching reading; and (3). be enrolled as senior high school teachers. Consequently, the sampling method used was homogeneous sampling. Open-ended questions consisting of six items were used to collect detailed information about EFL teachers’ perceptions following the teaching of reading materials integrated with local culture. The findings showed that by integrating local wisdom into reading materials not only improve language learning but also can enhance teachers’ teaching utilities, teaching strategies, and teaching engagement because it can be seen from the teachers’ responses more the teaching material cooperating local culture had significant contribution in their teaching material than obstacle, in teaching strategies by applying media in the form of teaching reading text materials cooperating local culture was more understandable, and teachers also felt more interactive with the students in teaching reading by cooperating local culture. Therefore, curriculum developers, educators, and policymakers should prioritize the inclusion of local wisdom in English language teaching to promote holistic and contextually relevant education. This approach developed both linguistic competence and cultural pride, particularly in multicultural regions such as Indonesia.